Influence of varying soil properties on evaluation of pile reliability under lateral loads - Kozubal, Janusz; Puła, Wojciech; Wyjadłowski, Marek; Bauer, Jerzy (Journal of Civil Engineering and Management, 2013)
A three dimensional probabilistic approach to analyzing laterally loaded piles is presented. Two typical subsurface models are used in the analyses: the first one consists of layered linear elastic soil where each layer has a random modulus of elasticity; while the second model takes the form of linear elastic soil with a random modulus of elasticity that increases with depth. Efficient step by step procedures for the reliability computation involving pile displacements are proposed. The solution is based on three-dimensional modeling by the finite element method. A series of results has been obtained for various values of elastic parameters of the soil. Next by a non-linear regression procedure a response surface is obtained. To get the final response surface allowing for a reliability analysis, an iterative algorithm based on the so-called design point concept is applied. The failure criterion is defined as the pile head displacement exceeding displacement threshold. The two cases of piles subjected to lateral load are computed. The paper illustrates the influence of the two distinct types of subsurface variability on the probabilistic analysis. A pronounced effect of the random variability of both the lateral force and the elastic modulus of the upper layer on reliability indices has been shown in results of numerical examples.